Insights into Magnetic Interactions in a Monodisperse Gd12Fe14 Metal Cluster. Issue 38 (9th August 2017) - Zheng, Xiu‐Ying; Zhang, Hui; Wang, Zhenxing; Liu, Pengxin; Du, Ming‐Hao; Han, Ying‐Zi; Wei, Rong‐Jia; Ouyang, Zhong‐Wen; Kong, Xiang‐Jian; Zhuang, Gui‐Lin; Long, La‐Sheng; Zheng, Lan‐Sun
Abstract: The largest Ln–Fe metal cluster [Gd12 Fe14 (μ3 ‐OH)12 (μ4 ‐OH)6 (μ4 ‐O)12 (TEOA)6 (CH3 COO)16 (H2 O)8 ]⋅(CH3 COO)2 (CH3 CN)2 ⋅(H2 O)20 (1 ) and the core–shell monodisperse metal cluster of1 a @SiO2 (1 a =[Gd12 Fe14 (μ3 ‐OH)12 (μ4 ‐OH)6 (μ4 ‐O)12 (TEOA)6 (CH3 COO)16 (H2 O)8 ] 2+ ) were prepared. Experimental and theoretical studies on the magnetic properties of1 and1 a @SiO2 reveal that encapsulation of one cluster into one silica nanosphere not only effectively decreases intermolecular magnetic interactions but also significantly increases the zero‐field splitting effect of the outer layer Fe 3+ ions. Abstract : Sphere of influence : The magnetic properties of Gd12 Fe14 and Gd12 Fe14 @SiO2 were investigated. The encapsulation of a single‐molecule cluster into one silica nanosphere influences not only the intermolecular magnetic interaction but also the zero‐field splitting effects of the Fe 3+ ions.